Sinonasal aspergillosis: Outcome after topical treatment in dogs with cribriform plate lysis. (29th June 2018) - Belda, Beatriz; Petrovitch, Nicholas; Mathews, Kyle G.
Abstract : Background: Cribriform lysis has been considered a contraindication for topical treatment of sinonasal aspergillosis (SNA) because of concerns about drug extravasation with resultant neurologic signs or death. Objective/Hypothesis: To describe dogs with SNA and cribriform plate lysis treated with topical antifungal medications. Our hypothesis was that the conventional dogma that topical therapy should be avoided in these cases is incorrect. Animals: Nine client‐owned dogs with SNA and lysis of the cribriform plate, lysis of the floor of a frontal sinus or both detected by computed tomography (CT). Methods: A retrospective review of medical records was performed. Dogs that met inclusion criteria (ie, SNA confirmed by at least 1 laboratory test, braincase affected on CT, and topical treatment applied) were included. Size of lesions, ancillary diagnostic test results, topical therapy, and adjuvant PO treatments were recorded. Outcome was determined by phone calls. Results: Four dogs were alive at the time of the manuscript submission with follow‐up ranging from 188 to 684 days without neurological signs observed. All dogs were discharged without major complication 1‐7 days postoperatively. One dog that had presented with a history of seizures experienced seizure activity 2 months after treatment. Conclusions and Clinical Importance: Topical therapy did not result in complications in these dogs in which lytic regions as large as 16 × 22 mm 2 were noted. Sinonasal aspergillosis associated lysis of the cribriform plate; lysis of the floor of a frontal sinus or both detected on CT is not necessarily a contraindication to topical therapy.